Identifying Students’ Learning Styles and Strategies in English Learning: Survey of SMK Negeri 1 Dobo - Fanumbi, Maria; Urlolo, Yulia Josina; Ngadjen, Syahdania Aini (MATAI: International Journal of Language Education, 2024)
This study explores the dominant learning styles of students at SMK Negeri 1 Dobo in learning English and the strategies they use to develop these styles. Recognizing students’ learning preferences is crucial for optimizing the educational experience and enhancing language acquisition. Through a descriptive quantitative approach, data were gathered from 30 students via questionnaires. The findings reveal that visual learning is the most preferred style among the students, who benefit from images, diagrams, and visual aids in language learning. To support their learning, students primarily use metacognitive strategies, which foster self-directed improvement, followed by knowledge strategies and occasional social strategies for practical application. These insights underscore the need for tailored instructional approaches that align with students’ visual preferences while integrating other methods to foster a comprehensive learning environment. This study provides valuable input for educators to align teaching methods with students’ dominant learning styles, thus enhancing engagement and learning outcomes.